Pulsed radiofrequency treatment of the superior hypogastric plexus in an interstitial cystitis patient with chronic pain and symptoms refractory to oral and intravesical medications and bladder hydrodistension: A case report. Issue 49 (December 2016) - Kim, Jong Hae; Kim, Eugene; Kim, Bong Il
Abstract: Rationale: A variety of therapeutic modalities are available for the treatment of interstitial cystitis. However, among them, the less invasive therapies are usually ineffective, whereas the invasive ones carry potential risks of serious side effects and complications. Pulsed radiofrequency (PRF) treatment of the superior hypogastric plexus may be an alternative to conventional treatments, as it provides nondestructive neuromodulation to the superior hypogastric plexus, which transmits the majority of pain signals from the pelvic viscera. Patient concerns: For 7 years, a 35-year-old female patient had been experiencing lower abdominal pain provoked by urinary bladder filling, perivulvar pain developing spontaneously during sleep or upon postural change, urinary urgency and frequency with 15- to 60-min intervals between urinations, and nocturia with 10 voids per night. Hydrodistension of the bladder, monthly intravesical administration of sterile sodium chondroitin sulfate, and oral medications including gabapentin and pentosan polysulfate had not been effective in managing the pain and symptoms. Diagnoses and interventions: Given the satisfactory result of a diagnostic block of the superior hypogastric plexus, 2 sessions of PRF treatment of the superior hypogastric plexus, which applied radiofrequency pulses with a pulse frequency of 2 Hz and a pulse width of 20 ms for 120 s twice per session to maintain the tissue temperature near the electrode at 42°C, were performed at a 6-month interval. Outcomes: This treatment relieved the pain and symptoms for 2 years and 6 months. Lessons: PRF treatment of the superior hypogastric plexus results in long-term improvements in the pain and symptoms associated with interstitial cystitis.